2012
DOI: 10.3928/21650799-20120726-03
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Among Workers in a Pediatric Health Care System

Abstract: Burnout among health care workers is recognized as an organizational risk contributing to absenteeism, presenteeism, excessive turnover, or illness, and may also manifest as decreased patient satisfaction. Pediatric health care may add stressors including worried parents of ill or dying children, child custody issues, child abuse, and workplace violence. The purpose of this study was to measure burnout among workers in a regional pediatric health care system and report whether burnout in a pediatric health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…5,[27][28][29] On the other hand, unlike the results of the present study, other studies found that the health-care personnel working with pediatric nurses had low burnout and compassion fatigue and moderate occupational satisfaction. 22,30,31 In the other studies compared to the present study, the participants' socio-demographic characteristics were mostly similar and similar methods were used, except for a study by Maytum, Heiman, Garwick, (2004). 32 The difference can be explained by the fact that the samples of these previous studies included other health-care professionals along with pediatric nurses, and that different measurement tools were used in these studies.…”
Section: Discussionmentioning
confidence: 95%
“…5,[27][28][29] On the other hand, unlike the results of the present study, other studies found that the health-care personnel working with pediatric nurses had low burnout and compassion fatigue and moderate occupational satisfaction. 22,30,31 In the other studies compared to the present study, the participants' socio-demographic characteristics were mostly similar and similar methods were used, except for a study by Maytum, Heiman, Garwick, (2004). 32 The difference can be explained by the fact that the samples of these previous studies included other health-care professionals along with pediatric nurses, and that different measurement tools were used in these studies.…”
Section: Discussionmentioning
confidence: 95%
“…A wide variety of research shows burnout exists in helping professions, especially in healthcare (Jacobs et al, 2012;Olson et al, 2015;Ptacek et al, 2013;Rodrigues et al, 2018). Healthcare workers are thought to be at risk for burnout due to their increased interactions with the public requiring socioemotional investment (Hoelscher & Ravert, 2021;Holloway & Wallinga, 1990).…”
Section: Burnoutmentioning
confidence: 99%
“…In general, healthcare workers have been found to be at increased risk for experiencing stress and trauma (Krisberg, 2018). Workplace stressors put healthcare professionals, including CCLS, at a greater risk for burnout (Holloway & Wallinga, 1990;Jacobs et al, 2012;Olson et al, 2015;Ptacek et al, 2013;Rodrigues et al, 2018). Burnout is a psychological condition resulting from extreme stress, often in the workplace, and professionals who are burned out feel apathy and indifference towards their work overall (Maslach & Jackson, 1982).…”
mentioning
confidence: 99%
“…Reduzir os níveis de burnout entre os trabalhadores é considerada uma medida essencial para melhorar o bem-estar dos trabalhadores e, possivelmente, contribuir para melhorias na segurança do paciente e na qualidade da assistência de enfermagem (118), incluindo ações visando o estabelecimento de estilos de vida saudáveis e equilíbrio entre aspectos pessoais e profissionais (119).…”
Section: Correlação Entre As Variáveis Do Ambiente Da Prática Profiss...unclassified
“…Mudanças positivas no ambiente da prática de enfermagem podem favorecer a saúde, segurança e bem-estar pessoal da equipe de enfermagem. Intervenções individuais e em grupo podem ter efeitos positivos na redução dos níveis de burnout (118,119,126,127) e melhorar a satisfação no trabalho (128). Consequentemente, espera-se maior atração e retenção de profissionais qualificados, menores índices de turnover, redução dos níveis de estresse relacionado ao trabalho, melhoria no trabalho em equipe e da satisfação no trabalho refletindo em qualidade e continuidade do cuidado ao paciente (50).…”
Section: Análise Do Modelo Teóricounclassified